Flight of White Peach Scale, Pseudαulαcαspis pentαgonα, Males and Time of Crawler Appearance in Northern Greece - Kyparissoudas, D.S. (ENTOMOLOGIA HELLENICA, 1992)
The seasonal Wight of white peach scale (WPS), Pseudaulacaspis pentagona Targioni-Tozzetti, males was studied during 1989, 1990 and 1991 in a peach orchard of Central Macedonia in Northern Greece by sex pheromone trapping. Three periods of male flight activity (mid-May to late June, mid-July to late August and early September to early November) were recorded annually. These flights correlated with three periods of crawler emergence (late June to early August, second ten days of August to third ten days of September, and mid-April to early May late May to early June of the next year). The first two periods of crawler activity came approximately 33 and 27 days after the beginning of the two first periods of male flight, respectively, while the crawlers corresponding to the third male flight emerged approximately 15 days after the deposition of the first spring eggs.